Revisión de tema: Rehabilitación Pulmonar en Pacientes con Cáncer de Pulmón - Molina Lopez, Cristobal Daniel (2019)
Lung cancer is one of the leading causes of cancer death in the world, being the main cause in 93 countries (1-6), this pathology has a survival of 15% in 5 year and at the beginning of the diagnosis 70 % of patients are non-operable (5). It is described that surgical treatment is the curative treatment of choice for this pathology (2,3,12,13), but not all patients are surgical at the time of diagnosis. Pulmonary rehabilitation is a multidisciplinary intervention that is based on evidence, is cost-effective (1,10), and for patients with lung cancer it has been seen that it can be based on the rehabilitation programs in COPD (20), this is safe and feasible in patients with advanced stages of the disease; another characteristic is that it can increase the number of operable cases (10). It takes 6 weeks to obtain substantial effects but from the 2-4 week physiological changes are seen (11,17,19,21)